In vivo 13C-MRI using SAMBADENA. - Andreas B Schmidt; Stephan Berner; Moritz Braig; Mirko Zimmermann; Jürgen Hennig; Dominik von Elverfeldt; Jan-Bernd Hövener (PLoS ONE, 2018)
Magnetic Resonance Imaging (MRI) is a powerful imaging tool but suffers from a low sensitivity that severely limits its use for detecting metabolism in vivo. Hyperpolarization (HP) methods have demonstrated MRI signal enhancement by several orders of magnitude, enabling the detection of metabolism with a sensitivity that was hitherto inaccessible. While it holds great promise, HP is typically relatively slow (hours), expensive (million $, €) and requires a dedicated device ("polarizer"). Recently, we introduced a new method that creates HP tracers without an external polarizer but within the MR-system itself based on parahydrogen induced polarization (PHIP): Synthesis Amid the Magnet Bore Allows Dramatically Enhanced Nuclear Alignment (SAMBADENA). To date, this method is the simplest and least cost-intensive method for hyperpolarized 13C-MRI. HP of P13C > 20% was demonstrated for 5mM tracer solutions previously. Here, we present a setup and procedure that enabled the first in vivo application of SAMBADENA: Within seconds, a hyperpolarized angiography tracer was produced and injected into an adult mouse. Subsequently, fast 13C-MRI was acquired which exhibited the vena cava, aorta and femoral arteries of the rodent. This first SAMBADENA in vivo 13C-angiography demonstrates the potential of the method as a fast, simple, low-cost alternative to produce HP-tracers to unlock the vast but hidden powers of MRI.